2018
DOI: 10.11606/issn.2317-0190.v25i1a158829
|View full text |Cite
|
Sign up to set email alerts
|

Mobilidade funcional, força, medo de cair, estilo e qualidade de vida em idosos praticantes de caminhada

Abstract: O processo de envelhecimento envolve modificações no desempenho locomotor que podem predispor os idosos a quedas e alterações na qualidade de vida. Objetivo: Comparar o medo de cair, mobilidade funcional, força de membros inferiores, estilo e qualidade de vida em idosos sedentários e praticantes caminhada. Método: Trata-se de estudo transversal observacional do qual participaram 51 idosos, 25 praticantes de caminhada (GCam) e 26 sedentários (GSed), submetidos à avaliação de mobilidade funcional (Timed Up and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In another study, it was found that older people practicing walking showed better functional mobility when compared to sedentary older people [ 41 ]. Such findings partially corroborate the present investigation, from which it was observed that a walking program performed for 16 weeks, twice a week, was sufficient to improve the tests of functional autonomy (W10M; SSP; SCMH; PTS; GI) and dynamic strength (FIC and MLLS).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was found that older people practicing walking showed better functional mobility when compared to sedentary older people [ 41 ]. Such findings partially corroborate the present investigation, from which it was observed that a walking program performed for 16 weeks, twice a week, was sufficient to improve the tests of functional autonomy (W10M; SSP; SCMH; PTS; GI) and dynamic strength (FIC and MLLS).…”
Section: Discussionmentioning
confidence: 99%
“…As well as, the impacts on the elderly health due to changes in locomotor performance, which can predispose these individuals to falls, changes in their functionality and quality of life. 18 Regarding the databases of the virtual library in which the studies were disseminated, the National Library of Medicine (MEDLINE) prevailed in greater proportion, with 47 articles (92.2%), while only four publications (7.8%) were identified It should be noted that MEDLINE is a relevant source of scientific dissemination and an important database of international literature in the medical and biomedical area, produced by the National Library of Medicine (NLM) in the United States of America, because it contains bibliographic references and abstracts of journals published in several countries.…”
Section: Resultsmentioning
confidence: 99%
“…34,35,48 Therefore, aerobic exercises and physical exercises for muscle strengthening have been indicated as strategies to improve physical performance, contributing to functional decline rehabilitation. 34,49 National and international studies 4,31,46,[50][51][52] also reported an association between functional dependence for the three ADLs with pre-frailty or frailty. In systematic reviews with metaanalysis, pre-frailty/frailty was also considered predictors for functional dependence in the elderly population.…”
Section: Ourmentioning
confidence: 93%